Germline mutations of renal cancer predisposition genes and clinical relevance in Chinese patients with sporadic, early‐onset disease. Issue 7 (12th December 2018) - Wu, Junlong; Wang, Hongkai; Ricketts, Christopher J.; Yang, Youfeng; Merino, Maria J.; Zhang, Hailiang; Shi, Guohai; Gan, Hualei; Linehan, W. Marston; Zhu, Yao; Ye, Dingwei
Abstract : Background: An inherited susceptibility to renal cancers is associated with multiple predisposing genes, but most screening tests are limited to patients with a family history. Next‐generation sequencing (NGS)–based multigene panels provide an efficient and adaptable tool for investigating pathogenic germline mutations on a larger scale. This study investigated the frequency of pathogenic germline mutations in renal cancer predisposition genes in patients with sporadic, early‐onset disease. Methods: An NGS‐based panel of 23 known and potential renal cancer predisposition genes was used to analyze germline mutations in 190 unrelated Chinese patients under the age of 45 years who presented with renal tumors. The detected variants were filtered for pathogenicity, and then their frequencies were calculated and correlated with clinical features. Germline variants of the fumarate hydratase ( FH ) and BRCA1‐associated protein 1 ( BAP1 ) genes were comprehensively analyzed because of their aggressive potential. Results: In total, 18 patients (9.5%) had germline mutations in 10 genes. Twelve of these 18 patients had alterations in renal cancer predisposition genes (6.3%), and 6 patients had mutations in potential predisposition genes such as BRCA1 / 2 . Notably, pathogenic mutation carriers had a significant family history in second‐degree relatives in comparison with those without pathogenic mutations ( P  < .001). Variants of unknown clinical significance in FH and BAP1 demonstrated evidence of additional somatic loss in tumors. Conclusions: In patients with early‐onset disease, a multigene panel identified a high pathogenic germline mutation rate in renal cancer predisposition genes. This study emphasizes the importance of screening patients with early‐onset disease for mutations in cancer predisposition genes. Germline screening should be encouraged in early‐onset patients to provide personalized medicine and improve patient outcomes. Abstract : The germline mutation rate of renal cancer predisposition genes (9.5%) is higher than ever estimated in patients with early‐onset disease. This study emphasizes the importance of screening these patients, regardless of family history, for personalized medicine.